A Comparative Study of Chosen Physical Fitness Components and Skill-Related Variables among Hockey Players of Gujarat - Desai Lilabhai I; Dr Bharat Chaudhari (International Journal of Scientific Research in Humanities and Social Sciences, 2025)
This study examines the physical fitness components and skill-related variables among hockey players in Gujarat, aiming to identify variations based on demographic and performance-related factors. A quantitative approach was employed, involving standardized tests to assess fitness components such as strength, endurance, and flexibility, as well as skill-related variables like speed, agility, and reaction time. The study revealed significant differences among players across various categories, offering insights into tailored training programs for performance enhancement. These findings contribute to understanding the role of region-specific factors in athletic development and highlight opportunities for targeted interventions in hockey training in Gujarat.